2018
DOI: 10.1371/journal.pone.0198684
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood characteristics and violence behind closed doors: The spatial overlap of child maltreatment and intimate partner violence

Abstract: In this study, we analyze first whether there is a common spatial distribution of child maltreatment (CM) and intimate partner violence (IPV), and second, whether the risks of CM and IPV are influenced by the same neighborhood characteristics, and if these risks spatially overlap. To this end we used geocoded data of CM referrals (N = 588) and IPV incidents (N = 1450) in the city of Valencia (Spain). As neighborhood proxies, we used 552 census block groups. Neighborhood characteristics analyzed at the aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 68 publications
3
47
1
Order By: Relevance
“…Advanced statistical methods are necessary to better understand causal pathways and effect mediators at the family, community, and policy levels of the socio-ecological framework, as well as of the mechanisms by which interventions exert their impact. Ecological, multilevel, and spatial analysis can clarify the geographic and social distribution of violent events 59,185,186 and identify the social and community conditions under which interventions and policies can be most effective.…”
Section: Future Directionsmentioning
confidence: 99%
“…Advanced statistical methods are necessary to better understand causal pathways and effect mediators at the family, community, and policy levels of the socio-ecological framework, as well as of the mechanisms by which interventions exert their impact. Ecological, multilevel, and spatial analysis can clarify the geographic and social distribution of violent events 59,185,186 and identify the social and community conditions under which interventions and policies can be most effective.…”
Section: Future Directionsmentioning
confidence: 99%
“…Yet, the vast majority of research and practice have focused on women and children separately [5,8], with few empirical studies on the connection or intersection of the two types of violence. Studies that do exist are primarily from high income countries and report that IPV and VAC often occur within the same families [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and neighborhoods [24], increasing risk of negative health effects [4,17,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…At an interpersonal level, social information processing conceptualizes the use of both types of violence due to attitudes accepting the use of violence in close relationships [36]. Intersecting violence may also be considered from a social disorganization theory perspective, where concentrated neighborhood disadvantage contributes to the occurrence of both IPV and VAC [24]. Other recent studies on intersecting IPV and VAC drawn upon a feminist framework, which contextualizes family violence and attitudes accepting violence in personal relationships within broader gender and power hierarchies [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Their approach could be used to improve detection of ecological variations in risk for child maltreatment, and to assess the effectiveness of the initiatives aimed at addressing risk (Gracia et al, 2017 ). The same authors later analyzed whether there was a common spatial distribution of child maltreatment and intimate partner violence and whether the risks of both forms of violence were influenced by the same neighborhood characteristics, and if these risks spatially overlapped (Gracia et al, 2018 ). Their model showed that certain neighborhood characteristics are associated with an increase in the risk of family violence, including both violence against children and against intimate partners (Gracia et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%